The Role Of Pancasila And Citizenship Education Teachers In Preventing Delinquency Students Of Class X - Reky Hoklae Aldo Siagian; Lukman Pardede; Monalisa Marta Siahaan (STABN RADEN WIJAYA WONOGIRI, 2021)
Student delinquency is a common problem in schools and can negatively impact character development, the learning process, and the overall educational climate. Pancasila and Citizenship Education ( PPKn ) plays a strategic role in shaping students' personalities and morals by instilling the noble values of Pancasila, legal norms, and civic responsibility. This study aims to analyze and describe the role of PPKn teachers in preventing student delinquency in schools. The method used in this study is a qualitative method with a descriptive approach. Data were obtained through observations, in-depth interviews with Civics and Citizenship Education ( PPKn ) teachers, and documentation of learning activities and student discipline. The results of the study indicate that Civics and Citizenship Education ( PPKn ) teachers fulfill their role not only as instructors but also as guides, counselors, and role models for students. Through values-based learning, moral discussions, and a personal approach, Civics and Citizenship Education ( PPKn ) teachers are able to instill discipline, responsibility, tolerance, and social awareness in students.